Framework of integration between Arabic Language and qira’at - Al-Muslim Mustapa (Penerbit Universiti Kebangsaan Malaysia, 2023)
Arabic language and Qira’at are two distinct disciplines of Islamic knowledge that possess their own areas of study and significant figures. However, due to the universality of knowledge, we can perceive the connection between these two fields from different angles. The primary objective of this synthesis research is to examine the reciprocal relationships between Arabic language and Qira’at throughout the history of knowledge development and finalize it in a theoretical framework. This qualitative, descriptive study utilizes document analysis as its methodology, gathering and synthesizing pertinent sources, notably primary sources related to Arabic language and Qira’at, to investigate their connections and mutual influences. Although Arabic language and Qira’at differ significantly in their definitions, the findings of this research suggest that there are interconnections between these two disciplines, which eventually led to the emergence of the science of Tawjih, a discipline that combines the use of Arabic language and Qira’at. Furthermore, the study reveals that Arabic language, particularly in syntax and morphology, has contributed to the comprehensiveness of Qira’at. Simultaneously, Qira’at has benefited Arabic language by exploring Arabic grammar and preserving some ancient Arabic dialects from extinction. There is no doubt that history shows a strong correlation between the two disciplines, despite their differences. The correlation between Arabic language and Qira’at is a complex and multifaceted relationship that has significant implications on future research.